Increasing Seismic Capacity of Existing Reinforced Concrete Buildings by the Use of FRP and Steel Fuse Elements - Cömert, Mustafa; Coşgun, Cumhur; Kesti, M. Gökhan; TÜRK, AHMET MURAT (My University, 2010)
Two of major problems for seismic rehabilitation of existing buildings are the necessity of evacuation of the occupants from the basis of the construction works and the limited time frame available for the actual construction site works. All of these problems often cause delays and cost overruns in the seismic rehabilitation projects. One possible way to eliminate these problems to a great extent is the use of FRP (fiber reinforced polymer) and steel fuse elements to improve seismic capacity. There is a huge stock of seismically deficient buildings that needs to be upgraded immediately according to the current Turkish Seismic Code (TSC 2007). The main aim of the paper is the examination of the possibility of using FRP and steel fuse elements on existing frame elements for seismic upgrading of the school and hospital buildings in Turkey. To investigate the possibility and effectiveness of the use of the hybrid system, a comparative study was performed. The comparison has made between typical framed RC building and the same building after retrofitting with FRP confinement and steel fuse elements around joints. By using nonlinear static (pushover) analysis, the performance levels of structural members were evaluated for both structures. This method seems as viable solution for the buildings considered in terms of safety and time.
Keywords: Reinforced concrete; Seismic rehabilitaiton; Retrofit; Cfrp; Steel fuse